Transmission of West Nile virus by Culex quinquefasciatus say infected with Culex Flavivirus Izabal. - Rebekah J Kent; Mary B Crabtree; Barry R Miller (Public Library of Science (PLoS), 2010)
BACKGROUND: The natural history and potential impact of mosquito-specific flaviviruses on the transmission efficiency of West Nile virus (WNV) is unknown. The objective of this study was to determine whether or not prior infection with Culex flavivirus (CxFV) Izabal altered the vector competence of Cx. quinquefasciatus Say for transmission of a co-circulating strain of West Nile virus (WNV) from Guatemala. METHODS AND FINDINGS: CxFV-negative Culex quinquefasciatus and those infected with CxFV Izabal by intrathoracic inoculation were administered WNV-infectious blood meals. Infection, dissemination, and transmission of WNV were measured by plaque titration on Vero cells of individual mosquito bodies, legs, or saliva, respectively, two weeks following WNV exposure. Additional groups of Cx. quinquefasciatus were intrathoracically inoculated with WNV alone or WNV+CxFV Izabal simultaneously, and saliva collected nine days post inoculation. Growth of WNV in Aedes albopictus C6/36 cells or Cx. quinquefasciatus was not inhibited by prior infection with CxFV Izabal. There was no significant difference in the vector competence of Cx. quinquefasciatus for WNV between mosquitoes uninfected or infected with CxFV Izabal across multiple WNV blood meal titers and two colonies of Cx. quinquefasciatus (p>0.05). However, significantly more Cx. quinquefasciatus from Honduras that were co-inoculated simultaneously with both viruses transmitted WNV than those inoculated with WNV alone (p = 0.0014). Co-inoculated mosquitoes that transmitted WNV also contained CxFV in their saliva, whereas mosquitoes inoculated with CxFV alone did not contain virus in their saliva. CONCLUSIONS: In the sequential infection experiments, prior infection with CxFV Izabal had no significant impact on WNV replication, infection, dissemination, or transmission by Cx. quinquefasciatus, however WNV transmission was enhanced in the Honduras colony when mosquitoes were inoculated simultaneously with both viruses.